Nanostructured antibacterial surfaces – What can be achieved?. (April 2022) - Linklater, Denver P.; Ivanova, Elena P.
Highlights: Detailed role that nanostructured surfaces can play in addressing antimicrobial resistance. Introducing promising nanomaterials for combatting biofilm formation on surfaces. Outlining the design of novel biocompatible nanomaterials to combat bacterial biofilm formation and infection. Graphical Abstract: ga1 Abstract: Nanomaterials have emerged as the new weapon in the arsenal to fight antimicrobial resistance (AMR). While antibiotics have played a major role in combating infectious diseases, AMR presents a new challenge for sustainability in global health, food security and development. Inspired by nature, recent trending research has demonstrated that specific nanoscale surface patterns can rupture and kill bacteria on contact. Nano-engineered surfaces have demonstrated good capacity to prevent bacterial attachment and biofilm formation (the precursor to infection) and could be used as a strategic disinfectant for medically and industrially relevant materials. This opinion paper provides an overview of the role of nanotechnologies, specifically nanostructured surfaces, in aiding the development of infection-resistant surfaces.